Modeling Hot Spot Motor Vehicle Theft Crime in Relation to Landuse and Settlement Patterns - Marwasta, Djaka; Suharsono, Suharsono (Forum Geografi, 2003)
The crowd of Yogyakarta urban has impacted its surrounding area, including Depok sub district, which is indicated by the rising of physical development, for example education facilities and settlements. The progress does not only bring positive impact, but also negative impact for instance the rising of crime number i.e. motor vehicle robbery. The aims of this research are 1) mapping motor vehicle robbery data as the distribution map and identifying motor vehicle robbery hot spot base on distrbution map; and 2) studying the correlation of motor vehicle robbery hot spot with physical environment phenomena, i.e. land use type and settlement pattern. The research method consists of two parts; they are motor vehicle robbery cluster analysis and the relation of motor vehicle robbery and physical environment analysis. Motor vehicle robbery cluster analysis is using distribution data, which analyzes the distribution into motor vehicle robbery hot spot with nearest neighbor tehnique. Contingency coefficient and frequency distribution analysis is used to analyze the correlation of motor vehicle robbery hot spot and physical environment. Contingency coefficient is used to study the relation of motor vehicle robbery hot spot polygon with physical environment condition, whereas frequency distribution is used to study the distribution of motor vehicle robbery in the hot spot with physical environment condition. Physical environment which consists of land use type, housing density, house regularity pattern, and the average of building size, are obtained from interpretation of black and white panchromatic aerial photograph year 2000, in the scale 1 : 20.000. the most motor vehicle robbery hot spot is found on the settlement area, 68,3% from 378 motor vehicle robbery cases in the hot spot. The seond level is found on the education area (16.4%). The most motor vehicle hot spot in the settlement is found on the hight density and irregular settlement, which have big size buildings. The calculation of contingency coefficient shows that there was a significant correlation between motor vehicle robbery hot spot with land use type and settlement pattern, but it has low correlation value. It means that land use type and settlement pattern have weak influence to the hot spot existence.